Evaluation of the Effectiveness of the Emotional Education Program EMO-ACTION within a Preschool Setting - María Fernández-Hawrylak; Davinia Heras-Sevilla; Amaya Cepa-Serrano (Universidad de Navarra, 2020)
The effectiveness of the Emotional Education Program EMO-ACTION (EMO-ACCIÓN) in the development of emotional skills and emotional strategies is evaluated, as well as empathy and problemsolving skills among preschool students. A sample of 123 children were enrolled in the 2nd year of preschool education, aged between 4 and 5 years old. A design of repeated pre-test/post-test measurements was applied to an experimental group (60 children) and a control group (63 children). The Recognition, Regulation, Empathy and Problem-Solving Scale (RRER) was administered before and after the educational intervention. The results confi rm that the program had a positive impact on the development of emotional skills in the children that took part in it. A significant increase was noted in emotional recognition, in emotional regulation, and in the identification, and resolution of problems.